Ivermectin Induces Oxidative Stress and DNA Damage in Breast Cancer Cells - GÜNAYDIN AKYILDIZ, AYŞENUR; Güler E. M.; Günaydın Akyıldız A. (My University, 2023)
Objective: Breast cancer (BC) remains to be one of the most diagnosed cancer types among women around the world. Drug repurposing is suggested to be a convenient alternative for drug development in cancer treatment. Ivermectin, the antiparasitic agent produced by the bacterium Streptomyces avermitilis, is currently being examined thoroughly in oncology and has begun to be seen as a potential drug candidate for BC therapy. However, studies are limited, and the exact anti-tumorigenic mechanism is not yet clarified in breast cancer. Methods: For elucidating the molecular mechanisms of Ivermectin’s potential anticancer effects, we have examined its in vitro effects on BC cells in terms of cell viability, intracellular ROS levels, glutathione levels, mitochondrial membrane potential, apoptosis, and DNA damage. Results: Ivermectin induces apoptosis via oxidative stress and DNA damage in BC cells. Conclusion: The in vitro mechanistic studies of promising anticancer agents for repurposing are essential guides for drug developers. For this purpose, ivermectin should be further studied as a drug candidate for its potential in the treatment of breast cancer.
Keywords: Ivermectin; breast cancer; drug repurposing; DNA damage; oxidative stress